Climate information services in the Mekong River Delta, Vietnam: Focus group discussion guide - Van, Lam Luong; Giraldo, Diana; Giles, James; Muller, Anna; Swaans, Kees; Ramirez Villegas, Julian (2024)
This guideline is part of the data collection process for the study, "Understanding rice farmers’ use of climate information services in the Mekong River Delta, Vietnam: A human-centered design approach." It outlines the methodology for conducting focus group discussions with farmers to explore their access to and use of agricultural information sources. The guideline details procedures for identifying the range of information channels and sources available to farmers and assesses the extent of their engagement with digital platforms for agricultural and climate-related information. Through this approach, we aim to gain insights into farmers' information preferences and their capacity to incorporate agro-climatic information services into decision-making processes for rice farming in the Mekong Delta.